Keragaman Genetik Pertumbuhan dan Hubungannya dengan Penetrasi Pilodyn pada Uji Provenansi-Keturunan Jabon (Neolamarkcia cadamba (Roxb) Bosser) di Parung Panjang, Bogor) (Genetic Variation of Growth and Its Relationship with Pilodyn Penetration on Provenance-Progeny Trial of Jabon (Neolamarkcia cadamba (Roxb) Bosser) at Parung Panjang, Bogor) - Anna, Nelly; Siregar, Iskandar Z; Supriyanto, Supriyanto; Karlinasari, Lina; Sudrajat, Dede J (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Jabon (Neolamarkcia cadamba (Roxb) Bosser) is a fast growing and preferred species as material for various wood industries. However, the growth and quality information of its wood is still limited. This study aims to assess the characteristics of growth, physical properties of wood, genetic parameters of growth and physical properties of wood, and its relationship with pilodyn penetration on provenance-progeny trial of jabon in Parung Panjang, Bogor. Measurement of growth characteristics was performed on height and diameter at breadst height (DBH), whereas the physical properties of wood (density, specific gravity, and moisture content) were performed using core samples (destructive methods) and density estimation with pilodyn (nondestructive method). Statistical analysis explains that there are significant differences between provenances in height, diameter, pilodyn penetration, density, and specific gravity, except for moisture content. The mean of plant survival percentage of 36 months old jabon was 52.8%. The relationship between growth character and the physical properties of wood with pilodyn penetration is negative and weak, except in moisture content, positive but weak. The estimation of individual heritability value ranges from 0.011 to 0.183, while heritability of the family ranges from 0.017 to 0.308.Keywords: growth, heritability, jabon, physical properties, pilodyn penetration